Clinical management of acute low back pain in elite and subelite rowers: a Delphi study of experienced and expert clinicians - Wilkie, K.; Thornton, J. S.; Vinther, A.; Trease, L.; McDonnell, S.-J.; Wilson, F. (British Journal of Sports Medicine, 2021)
OBJECTIVES: Rowing-related low back pain (LBP) is common but published management research is lacking. This study aims to establish assessment and management behaviours and beliefs of experienced and expert clinicians when elite and subelite rowers present with an acute episode of LBP; second, to investigate how management differs for developing and masters rowers. This original research is intended to be used to develop rowing-related LBP management guidelines.